The Prevalence of Functional Gastrointestinal Disorders in the Chinese Air Force Population - Wenming Wu; Xu Guo; Yunsheng Yang; Lihua Peng; Gaoping Mao; Hyder Qurratulain; Weifeng Wang; Gang Sun (Gastroenterology Research and Practice)
Background. Functional gastrointestinal disorders (FGIDs) are common in the general population worldwide. However, there is paucity of large sale surveys for prevalence of FGID in the military personnel. Methods. It is a cross-sectional study, using Rome III criteria for the diagnosis of FGID among the Chinese Air Force (CAF) workers. Results. Of 4633 registered male subjects, there were 818 (16.4%) air crew and 4170 (83.6%) ground personnel. FGIDs were identified in 1088 (23.48%) of cases. It was more prevalent in the ground personnel than air crew (24.02% versus 20.33%; ). Based on Rome III criteria, the commonest disease category was functional gastroduodenal disorder (37.4%), whereas functional nausea and vomiting disorder (FNV) was the most frequent overall diagnosis. Functional dyspepsia (FD) with irritable bowel syndrome (IBS) was the leading FGIDs' overlap (3.9%). Conclusion. FGIDs in CAF population are rather underestimated. This necessitates preventive strategies according to job characteristics.